Evaluating the cooperative and family farm programs in China: A rural governance perspective. (December 2018) - Shen, Mingrui; Shen, Jianfa
Highlights: Changes of farming governance in rural China are largely understudied. Two-tier farming model is favored and under test. Programs do benefit farmers' participation and income boosting. Social service and profit allocation in practice reveal a pseudo two-tier model. Abstract: Agriculture and land policy in China are transitioning from a market-oriented model into one with more balance. Accordingly, farming governance at the grassroots is also undergoing a transformation. Underpinned by state-led programs, policies have been implemented supporting a new two-tier model unifying cooperatives and family farms. In the two-tier model, the family farm is designated as the basic unit of farming while the cooperative offers social services to its farm members. Using a case study in Xinhui village in Nanjing, this paper unravels the organizational changes in farming initiated by these programs, as well as the extent to which the two-tier model is accomplished in practice. It is found that the new model benefits agricultural production by increasing farmers' participation and boosting their income. However, the empirical study also reveals a pseudo two-tier model. When examining the main criteria of social services and profit allocation, it is apparent that the cooperative functions more like a private company controlled by a former village official, rather than a voluntary association of farmers for their mutual benefit. Our research suggests that rigorous monitoring of land-related program implementation, as well as building a participation ethos at the grassroots, should have a more central role in policy-making.